2017
DOI: 10.1016/j.diabres.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of PCSK2 coding variants: A founder effect in the Old Order Amish population

Abstract: Aims In humans, noncoding variants of PCSK2, the gene encoding prohormone convertase 2 (PC2), have been previously associated with risk for and age of onset of type 2 diabetes (T2D). The aims of this study were to identify coding variants in PCSK2; to determine their possible association with glucose handling; and to determine functional outcomes for coding variants in biochemical studies. Methods Exome-wide genotyping was performed on 1725 Old Order Amish (OOA) subjects. PCSK2 coding variants were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Order Amish population (R430W variant rs200711626). 23 Although not significant (likely due to low power from infrequency of the allele), R430W was almost twice as prevalent in T2D individuals within this population. Further characterization of this allele found no difference in enzymatic activity or secretion, although R430W did broaden the PC2 pH optimum suggesting it induces a mild conformational change.…”
Section: Ants a Non-synonymous Pcsk2 Variant Was Found Enriched In Amentioning
confidence: 65%
See 1 more Smart Citation
“…Order Amish population (R430W variant rs200711626). 23 Although not significant (likely due to low power from infrequency of the allele), R430W was almost twice as prevalent in T2D individuals within this population. Further characterization of this allele found no difference in enzymatic activity or secretion, although R430W did broaden the PC2 pH optimum suggesting it induces a mild conformational change.…”
Section: Ants a Non-synonymous Pcsk2 Variant Was Found Enriched In Amentioning
confidence: 65%
“…PCSK2 polymorphisms may not be as well characterized as PCSK1 polymorphisms due in part to the rarity of PCSK2 protein‐coding variants. A non‐synonymous PCSK2 variant was found enriched in an Old Order Amish population (R430W variant rs200711626) . Although not significant (likely due to low power from infrequency of the allele), R430W was almost twice as prevalent in T2D individuals within this population.…”
Section: Prohormone Convertasementioning
confidence: 76%
“…In addition, common heterozygous PC1/3 mutations that cause partial loss of function contribute to variations in human BMI and plasma proinsulin and are associated with impaired regulation of plasma glucose levels (5). Genome-wide association studies have found associations between several common variants in the gene encoding human PC2 and diabetes risk and related traits in human populations (6,7).…”
mentioning
confidence: 99%
“…In addition, several polymorphisms and rare heterozygous mutations in the human PCSK1 gene (encoding for PC1/3) have been associated with an increased risk of obesity [ [14] , [15] , [16] ]. So far there are no reported PCSK2 (encoding for PC2) null patients, but several studies have associated PCSK2 SNPs with type 2 diabetes risk [ [17] , [18] , [19] ]. In this regard, Pcsk2 knockout mice have chronic mild hypoglycemia and hyperplasia of the pancreatic α-cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%